PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TYPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN GAMES EDUKASI BAAMBOOZLE TERHADAP PENGUASAAN KONSEP UNSUR-UNSUR INTRINSIK CERITA ANAK - Permata Sari, Anugerah; Kurniaman, Otang; Zufriady (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of Indonesian language in grade V students of SDN 79 Pekanbaru which have not met the criteria for achieving learning objectives (KKTP). The low learning outcomes are caused by the use of Indonesian language learning models and media that are less varied so that they have an impact on student learning outcomes. This study aims to determine the effect of using the Cooperative Learning Type Teams Game Tournament (TGT) learning model assisted by baamboozle educational games on mastery of the concept of intrinsic elements of children's stories. This type of research is quantitative research with experimental method with One Group Pretest-Posttest Design. The sample in this study amounted to 20 students. Data collection techniques using test techniques. The research test instrument is a multiple choice question that has been tested for validity, reliability, difficulty level, and question differentiation. Based on the results of the study, the average pretest score was 66 and the average posttest score was 85 which showed an increase. and the results of hypothesis testing using the Paired Sample T Test test which obtained a significance value (2-tailed) of >.001 so that Ho was rejected and Ha was accepted. As well as the results of the N-Gain test, the obtained gain score is 0.5757 which is included in the moderate category and the gain percent of 57.5707% is included in the moderately effective category.